Startegic Decision Making to Enhance Film Distribution Channel and Minimize Lack of Cinema Screen Problem in Indonesia - Dian Alanudin (Syntax Idea)
In Indonesia, the majority of film makers are independent film producers who perform all phases of filmmaking from development to distribution functions. Indonesia has significant film market potential, with large population and increasing middle class income, but currently Indonesia has only 1117 theaters with one market category, the middle-up class. Many Indonesian films suffering from financial loss and this sector considered as a high-risk investment. Objective of these research is find solutions to enhance movie distribution channel and minimize the lack of cinema screen problem in Indonesia. The research methodology used in this paper is qualitative by interview and observation. These research will be analyzed from an external environment and industry perspective using PESTEL and Porter's 5 Forces. Fishbone, Stakeholder Analysis, and Behavior Over Time Graph are used to find the root causes, identify key player, and pattern of existing conditions. In a complex problem situation, strategic decision making is analyze through system thinking approach. Government intervention, keyplayer innovations, cross promotion, technology can be identified to improve and change system behavior to these complex problems. For solution and recommendation, web-based integrated system as a components interrelationship will balance the performance, productivity, resources, and create many door opportunities for all stakeholders.